CRISPR/Cas- and Topical RNAi-Based Technologies for Crop Management and Improvement: Reviewing the Risk Assessment and Challenges Towards a More Sustainable Agriculture - Touzdjian Pinheiro Kohlrausch Távora, Fabiano; de Assis dos Santos Diniz, Francisco; de Moraes Rêgo-Machado, Camila; Chagas Freitas, Natália; Barbosa Monteiro Arraes, Fabrício; Chumbinho de Andrade, Eduardo; Furtado, Leila Lourenço; Osiro, Karen Ofuji; Lima de Sousa, Natália; Cardoso, Thiago Bérgamo; Márcia Mertz Henning, Liliane; Abrão de Oliveira Molinari, Patrícia; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated gene (Cas) system and RNA interference (RNAi)-based non-transgenic approaches are powerful technologies capable of revolutionizing plant research and breeding. In recent years, the use of these modern technologies has been explored in various sectors of agriculture, introducing or improving important agronomic traits in plant crops, such as increased yield, nutritional quality, abiotic- and, mostly, biotic-stress resistance. However, the limitations of each technique, public perception, and regulatory aspects are hindering its wide adoption for the development of new crop varieties or products. In an attempt to reverse these mishaps, scientists have been researching alternatives to increase the specificity, uptake, and stability of the CRISPR and RNAi system components in the target organism, as well as to reduce the chance of toxicity in nontarget organisms to minimize environmental risk, health problems, and regulatory issues. In this review, we discuss several aspects related to risk assessment, toxicity, and advances in the use of CRISPR/Cas and topical RNAi-based technologies in crop management and breeding. The present study also highlights the advantages and possible drawbacks of each technology, provides a brief overview of how to circumvent the off-target occurrence, the strategies to increase on-target specificity, the harm/benefits of association with nanotechnology, the public perception of the available techniques, worldwide regulatory frameworks regarding topical RNAi and CRISPR technologies, and, lastly, presents successful case studies of biotechnological solutions derived from both technologies, raising potential challenges to reach the market and being social and environmentally safe.